Younger age of dementia diagnosis in a Hispanic population in southern California. (29th January 2014) - Fitten, L. Jaime; Ortiz, Freddy; Fairbanks, Lynn; Bartzokis, George; Lu, Po; Klein, Eric; Coppola, Giovanni; Ringman, John
<x xml:space="preserve">Abstract</x> Objective Prior studies of US Hispanics, largely performed on the East Coast, have found a younger age of dementia onset than in White non‐Hispanics. We performed a cross‐sectional study to examine clinical and sociodemographic variables associated with age of dementia diagnosis in older Hispanics and White, non‐Hispanics in southern California. Methods Two hundred ninety (110 Hispanic and 180 White non‐Hispanic) community dwelling, cognitively symptomatic subjects, aged 50 years and older, were assessed and diagnosed with probable Alzheimer's disease or probable vascular dementia. Apolipoprotein E (APOE) genotype was assessed in a subset of cases. Analysis of variance and multiple stepwise linear regression were used to assess main effects and interactions of ethnicity with dementia severity (indexed by mini mental state examination scores) and other sociodemographic and clinical variables on age of dementia diagnosis. Results Hispanics were younger by an average of 4 years at the time of diagnosis, regardless of dementia subtype, despite a similar prevalence of the APOE ε4 genotype. The earlier age at diagnosis for Hispanics was not explained by gender, dementia severity, years of education, history of hypercholesterolemia, hypertension, or diabetes. Only ethnicity was significantly associated with age of onset. Conclusions These findings confirm that US Hispanics living in the southwestern USA tend to be younger at the time of dementia diagnosis than their White non‐Hispanic counterparts. As this is not explained by the presence of the APOE ε4 genotype, further studies should explore other cultural, medical, or genetic risk factors influencing the age of dementia onset in this population. Copyright © 2014 John Wiley & Sons, Ltd.